2006
DOI: 10.1002/jssc.200600139
|View full text |Cite
|
Sign up to set email alerts
|

Determination of amphetamines in human urine by liquid chromatography with fluorimetric detection using a solid‐phase extraction procedure

Abstract: A precise and feasible HPLC method has been developed for the analysis of amphetamine (AMPH), methamphetamine (MAMPH) and methylenedioxymethamphetamine (MDMA, ecstasy) in human urine. A chromatographic run on a C8 Genesis (150 mm x 4.6 mm, 5 microm) column maintained at 30 degrees C lasts about 17 min, using a mobile phase composed of ACN (12%) and a pH 2.5 phosphate buffer (88%) containing 0.3% triethylamine. Mirtazapine was used as the internal standard. Good linearity was found in the 100-2000 ng/mL concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In addition to UV detection or DAD as alternatives to MS as a detector for LC, a few laboratories utilize derivatization techniques to make the drugs suitable for fluorescence detection. Fluorescence detection (FD) is exploited in GHB analysis (Zacharis et al ., 2008) and in quantification of MA and/or MDMA (Bugamelli et al ., 2006; Chafer‐Pericas et al ., 2004; Kaddoumi et al ., 2004; Nakamura et al ., 2006; Wada et al ., 2005). When MS is not an available detection technique, FD can provide selectivity over UV but does not always provide a sensitivity advantage (see Tables 2 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to UV detection or DAD as alternatives to MS as a detector for LC, a few laboratories utilize derivatization techniques to make the drugs suitable for fluorescence detection. Fluorescence detection (FD) is exploited in GHB analysis (Zacharis et al ., 2008) and in quantification of MA and/or MDMA (Bugamelli et al ., 2006; Chafer‐Pericas et al ., 2004; Kaddoumi et al ., 2004; Nakamura et al ., 2006; Wada et al ., 2005). When MS is not an available detection technique, FD can provide selectivity over UV but does not always provide a sensitivity advantage (see Tables 2 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…The LLOQ in this assay represents a 75-fold increase in sensitivity over UV-assays previously reported by these authors. In 2006, Bugamelli et al [42] reported the quantification of a drug of abuse: amphetamine in human urine. The popularity of amphetamine, and its analogues such as ecstasy, can be attributed to their psychotropic effects.…”
Section: Other Disordersmentioning
confidence: 99%
“…The escalation of the abuse of these drugs has caused serious health and social problems [23]. In response to a growing demand for reliable evidence of AMPs and/or KET use, qualitative and quantitative detection of AMPs and/or KET in biological matrices has been developed using a variety of techniques such as gas chromatography (GC), gas chromatography-mass spectrometry (GC-MS), high-performance liquid chromatography (HPLC), and liquid chromatography-mass spectrometry (LC-MS) [23][24][25][26][27][28][29][30][31]. To meet the growing demands of separation ability and reductions in organic solvent consumption, capillary electrophoresis (CE) has recently become more and more popular and has been extensively applied in the analysis of illegal drugs in court and clinical diagnosis [32,33].…”
Section: Introductionmentioning
confidence: 99%